User-driven efforts in creating knowledge graph information system. Issue 2 (17th April 2020) - Gardasevic, Stanislava
Abstract : Purpose: This paper presents the results of a qualitative study that involved students of an interdisciplinary PhD program. The study objective was to gather requirements to create a knowledge graph information system. The purpose of this study was to determine information-seeking practices and information needs of this community, to inform the functionalities of a proposed system, intended to help students with relevant resource discovery and decision-making. Design/methodology/approach: The study design included semi-structured interviews with eight members of the community, followed by a website usability study with the same student participants. Findings: Two main information-seeking styles are recognized and reported through user personas of international and domestic (USA) students. The findings show that the useful information resides within the community and not so much on the program website. Students rely on peer communication, although they report lack of opportunities to connect. Students' information needs and information seeking are dependent on their progress through the program, as well as their motivation and the projected timeline. Practical implications: Considering the current information needs and practices, a knowledge graph hosting both information on social networks and the knowledge produced by the activities of the community members would be useful. By recording data on their activities (for example, collaboration with professors and coursework), students would reveal further useful system functionalities and facilitate transfer of tacit knowledge. Originality/value: Aside from the practical value of this research that is directly influencing the design of a system, it contributes to the body of knowledge on interdisciplinary PhD programs.